Aspirin and Infection: A Narrative Review - Stefano Di Bella; Roberto Luzzati; Luigi Principe; Verena Zerbato; Elisa Meroni; Mauro Giuffrè; Lory Saveria Crocè; Marco Merlo; Maria Perotto; Elisabetta Dolso; Cristina Maurel; Antonio Lovecchio; et al. (Biomedicines, 2022)
Acetylsalicylic acid (ASA) is one of the most commonly used drugs in the world. It derives from the extract of white willow bark, whose therapeutic potential was known in Egypt since 1534 BC. ASA’s pharmacological effects are historically considered secondary to its anti-inflammatory, platelet-inhibiting properties; however, human studies demonstrating a pro-inflammatory effect of ASA exist. It is likely that we are aware of only part of ASA’s mechanisms of action; moreover, the clinical effect is largely dependent on dosages. During the past few decades, evidence of the anti-infective properties of ASA has emerged. We performed a review of such research in order to provide a comprehensive overview of ASA and viral, bacterial, fungal and parasitic infections, as well as ASA’s antibiofilm properties.